Strategi Komunikasi Pemasaran Dalam Menarik Minat Calon Jemaah Pada Program Tabungan Umroh PT. Safarindo Albarokah - Halimah Tussadiyah (Universitas Muhammadiyah Sumatera Utara, 2026)
This study examines the marketing communication strategy implemented by PT Safarindo Albarokah in attracting prospective pilgrims to participate in the umrah savings program. The increasing public interest in performing umrah, coupled with financial limitations, has encouraged the emergence of savings-based programs as an alternative solution. This research uses a qualitative descriptive approach with an interpretive paradigm. Data were collected through in-depth interviews, observation, and documentation involving internal company informants and prospective pilgrims. Data analysis employed the interactive model of Miles and Huberman, including data collection, reduction, display, and conclusion drawing. The findings indicate that PT Safarindo Albarokah applies marketing communication strategies through the marketing mix (4P), namely product, price, place, and promotion. The company emphasizes transparent information delivery, flexible savings schemes, strategic service accessibility, and the use of both direct communication and digital media. These strategies contribute to building trust, increasing understanding, and encouraging interest among prospective pilgrims. The study concludes that effective communication strategies play a significant role in influencing public interest and decision-making toward umrah savings programs.This study examines the marketing communication strategy implemented by PT Safarindo Albarokah in attracting prospective pilgrims to participate in the umrah savings program. The increasing public interest in performing umrah, coupled with financial limitations, has encouraged the emergence of savings-based programs as an alternative solution. This research uses a qualitative descriptive approach with an interpretive paradigm. Data were collected through in-depth interviews, observation, and documentation involving internal company informants and prospective pilgrims. Data analysis employed the interactive model of Miles and Huberman, including data collection, reduction, display, and conclusion drawing. The findings indicate that PT Safarindo Albarokah applies marketing communication strategies through the marketing mix (4P), namely product, price, place, and promotion. The company emphasizes transparent information delivery, flexible savings schemes, strategic service accessibility, and the use of both direct communication and digital media. These strategies contribute to building trust, increasing understanding, and encouraging interest among prospective pilgrims. The study concludes that effective communication strategies play a significant role in influencing public interest and decision-making toward umrah savings programs